Gambaran Tingkat Pengetahuan tentang Pencegahan Luka pada Penderita Diabetes Mellitus (DM) - Eva Oktaviani; Siswoto Hadi Prayitno; Rizki Yulia Purwitaningtyas (Jurnal Ilmiah Kesehatan Rustida, 2021)
Diabetes mellitus is a disorder of carbohydrate, fat and protein metabolism caused by abnormal performance of insulin in the body, causing hyperglycemia. Diabetes causes various complications in the body. The most common complication in DM sufferers is diabetic ulcers which end in amputation (30%). This study aims to provide an overview of the level of knowledge about wound prevention in DM sufferers in Tegalharjo Village. The research design used a quantitative descriptive method with a total sampling technique adjusted for the exclusion and inclusion criteria. Respondents in this study amounted to 45 people. Data collection was carried out by means of a questionnaire that had been tested by previous researchers. The results showed that the majority of DM sufferers in Tegalharjo Village had enough knowledge with 21 respondents (46.7%), 15 respondents (33.3%) had good knowledge, and 9 respondents (20%) lacked knowledge. Data analysis in this study used univariate analysis because it only wanted to describe 1 variable, namely the level of knowledge about wound prevention. Knowledge possessed by DM sufferers can be a domain in behavior. However, the application of knowledge also requires education and family support so that DM sufferers are able to implement proper wound prevention.